How can it be [compact disc] - Daigle, Lauren (Centricity Music, 2015)
Building upon her five song EP, Lauren Daigle's first full length release is big, emotive, passionate pop that also features vulnerable and heartfelt worship. It also includes a collaboration with All Sons & Daughters.